2022
DOI: 10.1136/heartjnl-2021-319596
|View full text |Cite
|
Sign up to set email alerts
|

Excessive daytime sleepiness: an emerging marker of cardiovascular risk

Abstract: Excessive daytime sleepiness (EDS) is classically viewed as a consequence of insufficient sleep or a symptom of sleep disorders. Epidemiological and clinical evidence have shown that patients reporting EDS in tandem with sleep disorders (e.g., obstructive sleep apnoea) are at greater cardiovascular risk than non-sleepy patients. While this may simply be attributable to EDS being present in patients with a more severe condition, treatment of sleep disorders does not consistently alleviate EDS, indicating potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 52 publications
1
12
0
1
Order By: Relevance
“…Excessive daytime sleepiness is an emerging marker of cardiovascular risk, a condition that shares joint mechanisms with HL (Bock et al 2022). Moreover, insomnia is associated with increased systemic inflammation and increased atherosclerosis, which would cause thickening of the blood vessel walls and narrowing of the lumen, which would hinder adequate blood supply (Javaheri & Redline 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive daytime sleepiness is an emerging marker of cardiovascular risk, a condition that shares joint mechanisms with HL (Bock et al 2022). Moreover, insomnia is associated with increased systemic inflammation and increased atherosclerosis, which would cause thickening of the blood vessel walls and narrowing of the lumen, which would hinder adequate blood supply (Javaheri & Redline 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these results suggest the potential role of cardiovascular burden in this association. Evidence from the literature has indicated that EDS was associated with metabolic diseases including obesity, diabetes mellitus, and hypertension (Akbaraly et al, 2015; Lindberg et al, 2007; Maugeri et al, 2018), and is a risk factor for cardiovascular morbidity and mortality (Bock et al, 2022; Ng et al, 2018). Given the well‐documented association between cardiovascular burden and dementia (Deckers et al, 2017; Kivipelto et al, 2005; Kuźma et al, 2018; Livingston et al, 2020; Wagner et al, 2018), it may be hypothesised that a poor cardiovascular health characterised by risky behaviours (smoking, physical inactivity, dietary unbalance), unhealthy biological risk factors (high blood lipids, high blood pressure, obesity, diabetes mellitus) and/or clinical vascular events might play a role in the association between EDS and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of sleep apnea, typically of the obstructive type, are associated with increased cardiovascular risk, notably increased risk of high blood pressure [ 7 ], increased vascular aging [ 8 ], heart failure [ 9 ], arrythmias [ 10 ], and stroke [ 11 ], effects that seem more correlated with hypoxia than with sleep fragmentation [ 10 , 12 ]. Sleep fragmentation, in contrast, correlates more with arousal disturbances and daytime sleepiness, although some authors have found higher cardiovascular risk in sleepy versus non sleepy OSA patients [ 10 , 13 ]. Timely diagnosis and treatment of OSA is imperative to the health and prognosis of millions.…”
Section: Introductionmentioning
confidence: 99%